The Colonizing Realities of Neoliberal Capitalism - LaMothe, Ryan (Pastoral psychology, 2016)
This article addresses the proliferation of neoliberal capitalism in the United States as a dominant social imaginary that has colonized the psyches of many U.S. citizens. The notion of 'colonization' is used as a heuristic device in combination with a pastoral interpretive lens to depict and understand the psychosocial dynamics resulting from the hegemonic realities of neoliberal capitalism. More particularly, it is argued that neoliberal capitalism, as the dominant social imaginary, (1) undermines and corrupts Christian (and humanist) myths, narratives, and rituals that maintain and enrich social and communal life, shared relational faith, and interpersonal care; (2) establishes a superior-inferior value system, rooted in the commodification of everyday life, that introduces an ontological falsehood in individuals' psyches and relationships; (3) leads to a corresponding internalization of foreignness; and (4) narrows the public and political space of appearances.